Gender differences in outcomes after left atrial appendage closure with Watchman FLX device: insights from the Italian-FLX registry - Bonanni, Michela; Frazzetto, Marco; Nardone, Annalisa; Meucci, Francesco; Musto, Carmine; Quaranta, Gaetano; Saccà, Salvatore; Bedogni, Francesco; Maffeo, Diego; Ugo, Fabrizio; Guarracini, Fabrizio; Bocuzzi, Giacomo; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Current studies have revealed gender-specific differences in cardiovascular outcomes following left atrial appendage closure (LAAC), showing varied results in complication rates and adverse events, especially in short-term assessments. As a result, a notable knowledge gap persists regarding how these differences directly affect the effectiveness and safety of LAAC procedures. The objective of this retrospective study was to examine the clinical outcomes LAAC in both women and men with the Watchman FLX device.: This retrospective multicenter study analyzes gender-specific outcomes in 650 patients who underwent LAAC with the Watchman FLX device between March 2019 and May 2022, drawn from the PAGE \* Arabic \* MERGEFORMAT 3 ITALIAN-FLX registry.Results: Findings reveal comparable rates of all-cause mortality, stroke, transient ischemic attack, and major bleeding between men and women at 12 months post-procedure. Notably, no significant gender differences are observed in periprocedural complications or device-related thrombosis and peridevice leak < 5 mm at 45 days post-procedure.In conclusion, this study highlights that (LAAC) with the Watchman FLX device demonstrates comparable clinical outcomes between genders at both short and long-term follow-up intervals. The findings suggest that gender-specific differences in peri-procedural complications may not significantly impact overall outcomes.